Masyarakat Anomie Di Era Mitos Mayadenawa Perspektif Psikologi Sastra - I G. M Swastya Dharma Pradnyan; Komang Wahyu Rustiani (Jayapangus Press, 2018)
The myth of Mayadenawa is an oral literature developed in Bali. Mayadenawa was a king in ancient Balinese times. The leadership of the Mayadenawa king deviates from the religious, cultural, and moral values ​​of society. Consequently, because of the contextual fear of the community, there is a sign that is reflected in the myth, about the situation of Anomi society. Psychologically, Anomi occurs due to factors of mental stress so that people are faced with the situation of all activities begin to deviate with the customs, traditions and ancestral cultures inherited in Bali. To reveal the Anomic factors that occur in the society of the mythical during the myth mayadenawa then, necessary analysis of the structure of each character who plays a role in the story. The naratologi structure of Greimas was done because, the theory was born from semiotic rectangles in this case, referring to the psychological semantics that occurred in society during the myth of Mayadenawa.